2023
DOI: 10.1039/d2qi02084j
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic ruthenium–nickel alloy nanostructure supported on nickel foam for efficient alkaline hydrogen evolution at large current density

Abstract: A ruthenium–nickel alloy nanostructure exhibits a low overpotential and excellent activity stability for the hydrogen evolution reaction in 1 M KOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…37 The most commonly used 3D porous metal foams are excellent current collectors and show intrinsic catalytic activity when combined with a monolithic catalyst due to their synergistic effect. [38][39][40][41][42] Especially, Ni foam based catalysts have demonstrated exceptional performance due to their high density of active sites and enhanced hydrogen gas evolution. 43,44 Many studies have shown that binary and ternary metal phosphates outperform unary transition metal phosphates.…”
Section: Introductionmentioning
confidence: 99%
“…37 The most commonly used 3D porous metal foams are excellent current collectors and show intrinsic catalytic activity when combined with a monolithic catalyst due to their synergistic effect. [38][39][40][41][42] Especially, Ni foam based catalysts have demonstrated exceptional performance due to their high density of active sites and enhanced hydrogen gas evolution. 43,44 Many studies have shown that binary and ternary metal phosphates outperform unary transition metal phosphates.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Moreover, the formation of RuNi alloys can not only facilitate the electron transfer but also regulate the electronic structure of Ru, precisely tuning the surface affinity for crucial reaction intermediates, thereby accelerating the kinetics of the alkaline HER. [28][29][30] Herein, we fabricate Au@RuNi core-shell NWs, utilizing ultrafine 1D Au NWs as hard templates, facilitating the successful epitaxial in situ growth of fcc-RuNi alloy shell layers on their surfaces. Thanks to the formation of the fcc-RuNi alloy shell layer and the distinctive 1D core-shell nanowire structure, the synthesized Au@RuNi core-shell NWs demonstrate good HER activity in alkaline media (1.0 M KOH).…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Moreover, the formation of RuNi alloys can not only facilitate the electron transfer but also regulate the electronic structure of Ru, precisely tuning the surface affinity for crucial reaction intermediates, thereby accelerating the kinetics of the alkaline HER. 28–30…”
Section: Introductionmentioning
confidence: 99%